Factors Affecting Smile Esthetics - Yasemen Boncuk Tüzgiray; Burçak Kaya (Turkish Journal of Orthodontics, 2013)

(untitled)
Smiling has been one of the areas that draw the interest of orthodontists due to esthetic concerns in recent years. It should be understood what an ideal smile is and which factors affect it, and these should certainly be reflected in the orthodontic treatment plan. The purpose of this review is to describe smiling and to examine factors affecting smile and smile evaluation methods.